1996
DOI: 10.1080/00913367.1996.10673509
|View full text |Cite
|
Sign up to set email alerts
|

Man to Man: A Content Analysis of Sole-Male Images in Male-Audience Magazines

Abstract: A content analysis is presented ofsole-male images appearing in advertisements obtained from Business Week, Esquire, GQ, Playboy, Rolling Stone, and Sports Illustrated for the year 1993. Only two previous studies have looked exclusively at male images in magazine advertisements. The specific objective of the study was to describe the physical characteristics of the men appearing alone in advertisements. Body characteristics, hairstyles, facial hair, body and head positionings, dimensions of eye contact, clothi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 28 publications
3
85
0
3
Order By: Relevance
“…The empty gaze occurs most often in this category (along with female celebrities). For men, this may signal not so much withdrawal as a masculine gaze towards far and potentially adventurous horizons (Kolbe & Albanese, 1996).…”
Section: Gender As Master Status? the Intersection Of Gender And Rolementioning
confidence: 99%
See 1 more Smart Citation
“…The empty gaze occurs most often in this category (along with female celebrities). For men, this may signal not so much withdrawal as a masculine gaze towards far and potentially adventurous horizons (Kolbe & Albanese, 1996).…”
Section: Gender As Master Status? the Intersection Of Gender And Rolementioning
confidence: 99%
“…Four other poses were expected to be typically male: eye contact, photographed en face (frontal image with both sides of nose visible), erect body, and active pose (the person in the image is engaged in an activity other than being photographed) (Hatton & Trautner, 2011;Kang, 1997;Kolbe & Albanese, 1996;Kress & van Leeuwen, 2006;Lindner, 2004;Mager & Helgerson, 2011). Because of the inconsistent findings regarding the relational variables in previous studies, we constructed four descriptive variables measuring company: alone, with child, in the company of (adult) women, or (adult) men.…”
Section: Variablesmentioning
confidence: 99%
“…Goffman showed that "every physical surround, every box for social gatherings, necessarily provides materials than can be used in the display of gender and the affirmation of gender identity" (1997,207). Standard advertising poses generally signal men's dominance over submissive women, be it through physical, financial, or psychological superiority (Kolbe and Albanese 1996;Nixon 1996;Schroeder and Borgerson 1998). By focusing upon behavior as performance he challenged the distinction between the image and lived experience.…”
Section: Advertising Consumption and Representationmentioning
confidence: 99%
“…The significance of content analysis in consumer behaviour research has been explained by many authors (Kassarjian, 1977;Sayre, 1992;Kolbe & J, 1996). For the purpose of consumer research, content analysis is defined as a method of analysis of communication messages using systematic system of counting items within established categories (Sayre, 1992).…”
Section: Methodsmentioning
confidence: 99%